The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0220500
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and persistence of aberrant promoter DNA methylation in benzene-exposed Chinese workers

Abstract: Aberrant DNA methylation patterns are common in cancers and environmental pollutant exposed subjects. Up to date, few studies have examined the aberrant DNA methylation patterns in benzene exposed workers. We recruited 141 benzene-exposed workers, including 83 benzene-exposed workers from a shoe factory in Wenzhou and 58 workers from a painting workshop in Wuhu, 35 workers in Wuhu were followed from 2009 to 2013, and 48 indoor workers as controls from Wenzhou. We used high-resolution melting (HRM) to quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In addition to genotoxic modifications, acquired epigenetic alterations may participate in benzene leukemogenesis [ 109 , 110 , 111 ], and numerous findings are more coherent with an epigenetic model for onset of benzene-AML in which modified homeostatic control in the BM niche, not cytogenetic damage, prevails in the initial elaboration of the leukemic stem cell phenotype, a system completely different from preceding models of clonal cytogenetic damage [ 112 ].…”
Section: Epigenetics Hematological Neoplasms and Benzenementioning
confidence: 99%
“…In addition to genotoxic modifications, acquired epigenetic alterations may participate in benzene leukemogenesis [ 109 , 110 , 111 ], and numerous findings are more coherent with an epigenetic model for onset of benzene-AML in which modified homeostatic control in the BM niche, not cytogenetic damage, prevails in the initial elaboration of the leukemic stem cell phenotype, a system completely different from preceding models of clonal cytogenetic damage [ 112 ].…”
Section: Epigenetics Hematological Neoplasms and Benzenementioning
confidence: 99%
“…Compromising the activity of DNA damage repair proteins leads to genomic instability (57,58), thus setting the stage for oncogenesis. In a study that measured benzene concentrations and methylation patterns of genes implicated in carcinogenesis in peripheral blood, investigators found a higher degree of methylation in the promotor region of MGMT in healthy, benzene-exposed workers compared with healthy, unexposed workers (59). As mentioned previously, certain SNPs in MGMT have been shown to interact with chlorinated solvent exposure to increase DLBCL risk, highlighting this gene as a key suspect in chemical exposure-mediated lymphomagenesis whose dysregulation may occur via several distinct mechanisms.…”
Section: Epigenetic Consequences Of Environmental Exposures In Dlbcl ...mentioning
confidence: 99%
“…This finding illustrates that the genetic damage induced by benzene exposure is still serious, even after leaving a benzene work environment. Consistent with our previous reports (Ren et al ., 2019), the workers had a high MN frequency after the benzene concentration was significantly reduced in a follow‐up study.…”
Section: Discussionmentioning
confidence: 93%